Adaptation of NEMO-LIM3 model for multigrid high resolution Arctic simulation. (September 2019) - Hvatov, Alexander; Nikitin, Nikolay O.; Kalyuzhnaya, Anna V.; Kosukhin, Sergey S.
Abstract: High-resolution regional hindcasting of ocean and sea ice plays an important role in the assessment of shipping and operational risks in the Arctic Ocean. The ice–ocean model NEMO-LIM3 was modified to improve its simulation quality for appropriate spatio-temporal resolutions. A multigrid model setup with connected coarse- (14 km) and fine-resolution (5 km) model configurations was devised. These two configurations were implemented and run separately. The resulting computational cost was lower when compared to that of the built-in AGRIF nesting system. Ice and tracer boundary-condition schemes were modified to achieve the correct interaction between coarse- and fine grids through a long ice-covered open boundary. An ice-restoring scheme was implemented to reduce spin-up time. The NEMO-LIM3 configuration described in this article provides more flexible and customisable tools for high-resolution regional Arctic simulations. Highlights: NEMO model multigrid Arctic seas simulation. Separate inflow–outflow FRS-Advection boundary conditions for tracers to increase the quality along wide open boundary. Quality of Arctic ice simulation can be increased with FRS-based ice drift boundary conditions implementation. Implementation of ice restoration procedure allows to reduce the ice spin-up time.